2005
DOI: 10.1002/pbc.20477
|View full text |Cite
|
Sign up to set email alerts
|

The prevention and treatment of bacterial infections in children with asplenia or hyposplenia: Practice considerations at the Hospital for Sick Children, Toronto

Abstract: Children born without a spleen or who have impaired splenic function, due to disease or splenectomy, are at significantly increased risk of life-threatening bacterial sepsis. The mainstays of prevention are education, immunization, and prophylactic antibiotics. The availability of conjugate 7-valent pneumococcal vaccines for use in children to age 9 years at least, as well as conjugate meningococcal C vaccine in some countries, for use beginning in infancy, appear to represent beneficial additions, but not sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 33 publications
0
33
0
14
Order By: Relevance
“…Further, the global spread of penicillin-resistant S. pneumoniae and the potential for selection of resistant organisms have diminished the enthusiasm for antibiotic prophylaxis. Educating individuals with complement deficiencies or splenectomies about their increased risk for serious, lifethreatening infections and the importance of seeking prompt medical attention for febrile illnesses is essential (360). A study in the Netherlands revealed that 43% of splenectomized patients had not received up-to-date information about the infection risks associated with their condition and that 50% were not aware of the need to contact a physician immediately in case of high fever (291).…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%
“…Further, the global spread of penicillin-resistant S. pneumoniae and the potential for selection of resistant organisms have diminished the enthusiasm for antibiotic prophylaxis. Educating individuals with complement deficiencies or splenectomies about their increased risk for serious, lifethreatening infections and the importance of seeking prompt medical attention for febrile illnesses is essential (360). A study in the Netherlands revealed that 43% of splenectomized patients had not received up-to-date information about the infection risks associated with their condition and that 50% were not aware of the need to contact a physician immediately in case of high fever (291).…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%
“…La principal indicación de esplenectomía en pediatría es los estados hiperesplénicos que dan cuenta de más de 50% de las esplenectomías, mientras que el trauma abdominal es indicación de 10 a 30% de las esplenectomías 3,4 . En la Tabla 1 se encuentran las condiciones clínicas en las cuales se puede llegar a considerar la esplenectomía quirúrgica.…”
Section: Causasunclassified
“…El pródromo generalmente es leve, consistente con un cuadro febril, en que el sello está dado por un deterioro clínico en el curso de horas, asociado a compromiso hemodinámico, coagulación intravascular diseminada y falla multiorgánica que no responde a medidas habituales y que puede simular una meningococcemia fulminante 1,5 . La incidencia real de SBF es desconocida pero las estimaciones derivadas de la observación de cohortes Infectología al Día muestran una incidencia anual de 0,23 a 0,42% post esplenectomía con un riesgo de 5% a lo largo de la vida 4,5,12,14 . La letalidad global es de 50 a 70% y puede descender a 10% con un tratamiento médico agresivo y precoz 5 ; la mayor tasa de mortalidad se da en el grupo de pacientes bajo 2 años de edad 3 .…”
Section: Sepsis Bacteriana Fulminanteunclassified
See 2 more Smart Citations